2014
DOI: 10.1016/j.clineuro.2014.08.037
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic third ventriculostomy in the management of hydrocephalus: Outcome analysis of 168 consecutive procedures

Abstract: a b s t r a c tBackground: Endoscopic third ventriculostomy (ETV) is the treatment of choice for obstructive hydrocephalus, but the outcome is still controversial in terms of age and aetiology. Methods: Between 1998 and 2011, 168 consecutive procedures were performed in 164 patients, primarily children (56% < 18 years of age and 35% < 2 years of age). The causes of obstructive hydrocephalus included tumoural pathology, Chiari malformation, congenital obstruction of the aqueduct, post-infectious and post-haemor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 99 publications
1
12
0
Order By: Relevance
“…Since the first descriptions of the treatment by Nishihara et al in 1996 [ 12 ], we reviewed the subsequent literature (excluding case reports) that has reported on the management of hydrocephalus associated with CIM via ETV [ 9 , 14 18 ] (Table 1 ). The success rate is not consistent and is in the range of 40–100%; in this study, it was 80%.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first descriptions of the treatment by Nishihara et al in 1996 [ 12 ], we reviewed the subsequent literature (excluding case reports) that has reported on the management of hydrocephalus associated with CIM via ETV [ 9 , 14 18 ] (Table 1 ). The success rate is not consistent and is in the range of 40–100%; in this study, it was 80%.…”
Section: Discussionmentioning
confidence: 99%
“…Our ETV success outcomes fall within the range of outcomes that have been previously reported by other centers. 1,13,18,29,33,36 Some of the highest efficacy data were presented by Woodworth et al, who observed immediate improvements in 89% versus 71% of patients who underwent primary and secondary ETV, respectively. 35 In a larger cohort of 129 patients, Jenkinson et al observed success rates of 83% and 67% in primary and secondary ETV groups, respectively.…”
Section: Efficacy Of Etv Treatmentmentioning
confidence: 97%
“…Previously, ETV/CPC success rates at other sites have been in the range from 40% to 70%. 5,11,15,22,23 Our rates are slightly lower than other established international pediatric neurosurgery training sites (75%), which may reflect several limitations in the management of hydrocephalus surgery in Haiti. Primarily, our series highlights outcomes for an intent-to-treat analysis, that is, patients with attempted ETV/CPC.…”
Section: Discussionmentioning
confidence: 55%